POTENSI HASIL UMBI DAN KADAR PATI PADA BEBERAPA VARIETAS UBIKAYU DENGAN SISTIM SAMBUNG (MUKIBAT) - Budhi Santoso Radjit; Nila Prasetiaswati (BUANA SAINS, 2011)
The experiment was conducted at Genteng experiment station during January – December 2008. The objective of the experiment is to evaluate yield potential and starch content on grafting cassava (mukibat system). The experiment was arranged in a randomized complet block design with three replication. The first factor are four cassava varieties (Adira 4, UJ-5, Kaspro and local Dampit). The grafting system and ordinary cassava as the second factor. The grafting cassava (mukibat) planted with kenong system (plant/hill), plant spacing 1,5 m x 1,5 m and ordinary cassava planted in flat bad system, plant spacing 100 cm x 60 cm The fertilitation were 300 kg Urea + 100 kg SP-36 + 100 kg KCl ha-1 and fertilation 5 t/ha. The weed control were two times ( at two and four month after planting). The result showed that Adira 4, UJ-5, Kaspro dan Lokal Dampit varieties yielded 90,4 – 99,67 t/ha, with grafting system (mukibat). While the ordinary system yielded 54,3 t – 61,87 t/ha. There are positif corelation among tuber number, tuber diameter and tuber weight per plant with tuber yield. The starch content on mukibat system decrease 0,7 – 2,23% compared with ordinary system. UJ-5 variety has relatively stabil starch content and higher comparing the other variety. The grafting system needs higher cost production (Rp 8.491.000,-) than ordinary system.(Rp 7.971.000,-). The benefit of grafting system increase up to 90,5% from ordinary system and B/C ratio was 4,1